Simultaneous observer-based fault detection and event-triggered consensus control for multi-agent systems. Issue 6 (April 2021) - Li, Shanglin; Chen, Yangzhou; Zhan, Jingyuan
Abstract: This paper is concerned with the problem of fault detection and consensus control via event-triggered scheme for a class of linear multi-agent systems subject to external disturbances. For the network of multi-agent systems with unknown faults and disturbances, the event-triggered consensus protocol and observer-based fault detection filter are designed simultaneously. Through the model transformation and decomposition, the specific design problem can be transformed into a multi-objective optimization problem by using a mixed H ∞ / H − method. Based on the Lyapunov-Krasovskii Theory and Projection Lemma, some sufficient conditions, which ensure the decomposed system is not only asymptotically stable, but also satisfies the prescribed optimization performance constraints, are derived in the form of linear matrix inequalities. Finally, two simulation examples are provided to verify the practicality and validity of the theoretical results.